Seasonal shifts and land-use impact: unveiling the gut microbiomes of bank voles ( Myodes glareolus) and common voles ( Microtus arvalis) - Kauer, Lea; Imholt, Christian; Jacob, Jens; Berens, Christian; Kühn, Ralph (FEMS Microbiology Ecology, 2024)
Abstract Gut microbial diversity influences the health and vitality of the host, yet it is itself affected by internal and external factors, including land-use. The impact of land-use practices on wild rodents’ gut microbiomes remains understudied, despite their abundance and potential as reservoirs for zoonotic pathogens. We examined the bacterial and fungal gut microbiomes of bank voles (Myodes glareolus) and common voles (Microtus arvalis) across grassland and forest habitats with varying land-use intensities and types. We collected rodents seasonally and used 16S rRNA and ITS amplicon sequencing for microbe identification. We found significant differences in alpha and beta diversities between the species, with M. arvalis exhibiting higher diversity. Seasonality emerged as a prominent factor influencing microbial diversity, with significant variations between sampling months. While land-use affects the gut microbiome, its impact is subordinate to seasonal variations. Differential abundance analysis underscores the dynamic nature of microbial composition, with seasonal changes playing a predominant role. Overall, our findings highlight the significant influence of seasonality on gut microbiome diversity and composition in wild rodents, reflecting dietary shifts associated with seasonal changes. Understanding the interplay between environmental factors and microbial communities in wild rodents enahnces our knowledge of ecosystem health and resilience, warranting further investigation.